POLA RELASI POLITIK ADMINISTRASI DALAM REKRUTMEN ELIT BIROKRASI - Elip Heldan, Mrs. (FIA UB, 2012)
To understanding the dynamic of administrative politic relational pattern in the bureaucracy elite recruitment, the role of political institution and bureaucracy institution, the constraints during interaction conduct, its implication to the bureaucracy performance, and the recommendation of a favorable administrative politic relational pattern. This review is expected to produce a balanced dynamic relational pattern. Method of research is qualitative study, with intensive observation to the research phenomena. Data collection technique is triangulation. Data analysis tool is Denscombe Model (2007).The research finding, The relational form will influence the political intervention tendency in the bureaucracy elite recruitment process. The bureaucracy elite (Echelon II) recruitment dynamic represents a regulation over the authority of local leadership. In fact, the candidate of bureaucracy elite must be through Local House of Representativesâ (DPRD) acknowledgement although the Regent still may consult with and ask for support from DPRD informally.As the local leaders are a position in the political domain, bureaucracy recruitment is made politically. Determining the strategic position of bureaucracy elite is more logic by considering the input and advice from the political domain, such as from local legislative institutions. This opportunity gives local legislative institutions to improve their political interest. This empowered political interest may develop intervention pattern and political actorâs pressure.